Mussel-Inspired Polydopamine-Based Multilayered Coatings for Enhanced Bone Formation - Wu, Hao; Zhao, Cancan; Lin, Kaili; Wang, Xudong (Frontiers in Bioengineering and Biotechnology, 2022)
Repairing bone defects remains a challenge in clinical practice and the application of artificial scaffolds can enhance local bone formation, but the function of unmodified scaffolds is limited. Considering different application scenarios, the scaffolds should be multifunctionalized to meet specific demands. Inspired by the superior adhesive property of mussels, polydopamine (PDA) has attracted extensive attention due to its universal capacity to assemble on all biomaterials and promote further adsorption of multiple external components to form PDA-based multilayered coatings with multifunctional property, which can induce synergistic enhancement of new bone formation, such as immunomodulation, angiogenesis, antibiosis and antitumor property. This review will summarize mussel-inspired PDA-based multilayered coatings for enhanced bone formation, including formation mechanism and biofunction of PDA coating, as well as different functional components. The synergistic enhancement of multiple functions for better bone formation will also be discussed. This review will inspire the design and fabrication of PDA-based multilayered coatings for different application scenarios and promote deeper understanding of their effect on bone formation, but more efforts should be made to achieve clinical translation. On this basis, we present a critical conclusion, and forecast the prospects of PDA-based multilayered coatings for bone regeneration.